1998
DOI: 10.1159/000030222
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Renal Cystic Disease and Adenocarcinoma following Renal Transplantation – A Current Urologic Perspective

Abstract: Two patients treated with chronic dialysis and renal transplantation developed acute hemorrhage from a native kidney. Bilateral native nephrectomy demonstrated acquired cystic disease and adenocarcinoma in each of the four kidneys. The etiology of acquired cystic kidney disease (ACKD) is unclear and its incidence increases with the duration of dialysis. ACKD patients have a propensity to develop adenomas and adenocarcinomas. The increased incidence of renal neoplasms in ACKD patients warrants careful radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…11,13,14,28 The role of the calcium oxalate crystals in the development of renal cell tumors in the context of acquired cystic disease of kidney is uncertain. 11,14,29 Immunohistochemical studies on acquired cystic disease-associated renal tumors are few, and mostly 33 described in abstract form FISH analyses with centromeric probes for chromosomes 1, 3, 7, and 17 on 10 tumors arising in end-stage renal disease, among which two acquired cystic kidney diseaseassociated tumors were included. They found that both tumors were disomic for chromosomes 1 and 3, whereas one had loss of chromosome 7 and the other showed loss of chromosome 17.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14,28 The role of the calcium oxalate crystals in the development of renal cell tumors in the context of acquired cystic disease of kidney is uncertain. 11,14,29 Immunohistochemical studies on acquired cystic disease-associated renal tumors are few, and mostly 33 described in abstract form FISH analyses with centromeric probes for chromosomes 1, 3, 7, and 17 on 10 tumors arising in end-stage renal disease, among which two acquired cystic kidney diseaseassociated tumors were included. They found that both tumors were disomic for chromosomes 1 and 3, whereas one had loss of chromosome 7 and the other showed loss of chromosome 17.…”
Section: Discussionmentioning
confidence: 99%
“…Even after transplantation periodic surveillance of the kidneys, both native and transplant, is warranted, although firm guidelines backed by hard data are not yet available [33,34].…”
Section: Transplantationmentioning
confidence: 99%
“…Von diesem hereditären Krankheitsbild ist die erworbene zystische Nierendysplasie (ACKD = aquired cystic kidney disease) zu unterscheiden, welche vornehmlich nach langjähriger Dialysetherapie beobachtet wird. In mehreren Untersuchungen (Patientenkollektive nach Nierentransplantation) wurde ebenfalls ein gehäuftes Auftreten von Nierenzellkarzinomen (6 -20 %) festgestellt [2,10,11,16,19], jedoch ist bislang unklar, ob die Tumorentstehung auf die Dialysebehandlung, die adjuvante Therapie zur Transplantation oder die Grunderkrankung zurückgeführt werden muß. Demgegenüber finden sich keine Berichte über eine Häufung von Urothelkarzinomen bei Patienten mit polyzystischen Nieren.…”
Section: Diskussionunclassified